Effectiveness of the Sequenced Type of Integrative Learning Model in Teaching Writing of West Wawonii Elementary School Students - Asdar; Muhammad Asdam; Nursamsilis Lutfin; Elsayani Grestiani Limbong; Tuan Nordin bin Tuan Kechik (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2024)
The objectives of this research are to find out the results of students' writing learning before and after participating in learning using the sequenced type integrative learning model. To find out students' activities in participating in learning using the sequenced type integrative learning model. And to determine students' responses to learning to write using a sequenced type integrative learning model. This research is categorized as quantitative descriptive research. In this study, the One Group Pretest-Posttest design was used, namely an experiment carried out with one group that was given a pretest before being given treatment. The findings show that the average fifth grade students gave a positive response to the implementation of the sequenced integrative learning model, where the average percentage of student responses was 89.5%. Thus, the response of students taught using this model can be said to be effective. Learning to write using a sequenced type integrative model can result in changes in students' activities and views towards learning to write as shown by the percentage of positive student responses of 78%. And after implementing the sequenced type integrative learning model have met the indicators of completeness of classical student learning outcomes, namely ≥ 75%. Moreover, it can be concluded that the teacher's ability to manage learning using the sequenced integrative learning model is said to be effective at SDN Wawonii Barat.